Analisis Efisiensi Strategi Optimalisasi Kemitraan Operasional bagi Perusahaan Kurir - Jamil, Abdul (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Operational partnership strategies in the courier industry provide benefits to companies through cost efficiency and business flexibility. However, from the partner's perspective, there are challenges such as income instability and minimal social security. The role of the government is crucial in regulating this scheme to create a balance of interests. The results of this study indicate that the benefits obtained by companies from operational partnership patterns in the courier industry are very significant, especially in terms of cost efficiency, operational flexibility, and the ability to expand market reach without having to make large investments. One of the main advantages faced by companies is the cost efficiency that can be achieved through the use of partners. In this partnership pattern, companies do not need to spend large fixed costs, such as monthly salaries and benefits that are usually given to permanent employees. On the other hand, partners who have freelance or independent status are only paid based on the number of deliveries they make. This allows companies to reduce fixed expenses, as well as adjust the number of partners to fluctuating business needs.